Intracranial Cysts: An Imagery Diagnostic Challenge - Alexandra Oprişan; Bogdan O. Popescu (The Scientific World Journal)
Intracerebral cysts and cystic appearing intracerebral masses are common findings at routine cerebral imaging examination. We discuss here the most interesting aspects of some intracerebral cysts encountered in medical practice in terms of imaging, clinical and pathological description, and problems of differential diagnosis. On an almost routine basis, the neurologists have to deal with such differentials. Therefore, we aim to mention here some of the frequently encountered diagnosis problems when a patient presents with a cystic cerebral mass.